Gender and geopolitics in 'secular time'. Issue 2 (1st March 2013) - Olson, Elizabeth
<x xml:space="preserve">Abstract</x> This article argues that gender must be central to our theorisations of emergent religious geopolitics. It does so through an engagement with Butler's reflections upon secular time (Butler J 2008 Secular politics, torture, and secular time The British Journal of Sociology 59 1–23), and the 'cultural reanimation' of Roman Catholic cultural underpinnings of French culture in the defence of the torture and maltreatment of Islamic bodies. Drawing from both the broader, tactical gender geopolitics of the Catholic Church and the embodied experiences of Catholic faithful in Latin America, the paper argues that the concept of cultural reanimation fails to capture the skilful way in which the Holy See asserts a gender theology that transcends the individual faithful body, through to the body of humanity. The ambiguous position of religious institutions in contemporary geopolitics as both cultural and political facilitates the construction of boundaries and territories that transcend and cut through the politics of the state.